Rio de muitos frutos: o quilombo compondo identidades em Ivaporunduva (Vale do Ribeira SP) - Costa, Antonio Carvalho (2011)
This work is about the process of forming identities in Ivaporunduva (Eldorado-SP) as a result of their struggle and recognition them as a remnant of Quilombo. In early 1990, communities in the Ribeira Valley (SP / PR) faced with the 'Article 68' ADCT as a possibility to stop the advancement of the interests that sought to install hydroelectric projects in the course of the Rio Ribeira de Iguape. Ivaporunduva starts composing his quilombola (maroon) identity as it articulated their struggle to oppose to the dams and in recognition of its territory through the Grupo de Mulheres de Eldorado (Women's Eldorado Group), Movimento dos Ameaçados por Barragens MOAB, (Movement of People Affected by Dams) and Associação Quilombola (maroon association). This movement mobilized universities, government agents and non-governmetal organization with the same purpose. With the work development, we tried to emphasize the new social roles that emerged within the community Ivaporunduva, as well as the readings from residents about the process that culminated in the public record of its Quilombola territory in 2010